FROM PRESIDENTIALISM TO PARLIAMENTARISM: PARLIAMENTARIZATION OF GOVERNMENT SYSTEMS IN KYRGYZSTAN, GEORGIA AND ARMENIA - BORISOV, Nikolay (CENTRAL ASIA AND THE CAUCASUS, 2018)
The article deals with the transformation of government forms in the post-Soviet states (Kyrgyzstan, Armenia, Georgia) towards parliamentarization on the basis of neo-institutional and comparative methods. The reasons for this transformation and the degree of its influence on the political process are analyzed.As a result of the changes, the presidents of Georgia, Armenia and Kyrgyzstan lost the most important powers, retaining, however, the status of the head of state. The electoral system for parliamentary elections in all three states has been replaced by a fully proportional one. The author comes to the conclusion that the changes in government forms and the electoral system were initiated by the ruling elites and are aimed not so much at improving the efficiency of public administration, but at preserving the power. However, the parliamentarization of government systems in the three post-Soviet states had a “capsizing” effect on the ruling elite in two cases (Armenia and Georgia), and in another case (Kyrgyzstan) it could lead to the removal of the former incumbent from the channels of influence on the incumbent President. In general, institutional reforms geared towards parliamentarization, combined with the transition to a proportional representation system, lead to the development of political competition and contribute to the institutionalization of party systems in the states considered.